Pendampingan Komunitas UMKM Batu Bata melalui Penggunaan Aplikasi Perhitungan Stock berbasis E-commerce di Desa Pasir Putih Ujung Kecamatan Talang Kelapa Kabupaten Banyuasin - Hendra Hadiwijaya; Febrianty Febrianty; Darmawi Darmawi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2019)
: Identification of problems faced by partners in the Daslan Brick Business Partners in Pasir Putih Village, Talang Kelapa District, Banyuasin Regency, namely: lack of knowledge about product marketing strategies because they are still waiting for buyers and stocking bricks. Based on priority issues that must be addressed, the solution offered to partners is to increase knowledge about the product marketing strategy through e-commerce that will be produced and training in the application of calculating brick stock that will make it easier to know the amount of brick stock and record sales / ordering transactions . The target of this service is to empower the Daslan Brick Business to become an independent business. After empowerment through appropriate technology produced and 8 (eight) months training and mentoring activities for Daslan Bata Business partners, the detailed target is to increase knowledge about product marketing strategies. The work procedures in this PKM are as follows: Appropriate Technology Development Phase (TTG) namely e-commerce web and brick stock calculation application, Training phase, namely: training on e-commerce usage and application of brick stock calculation, and PKM Evaluation stage. These PKM results can increase partner business competitiveness by a minimum of 60%; the application of science and technology by 75%; and there was an increase in knowledge and skills by 70%.